A prioritization protocol for coastal wetland restoration on Molokaʻi, Hawaiʻi - Drexler, Judith Z.; Raine, Helen; Jacobi, James D.; House, Sally; Lima, Pūlama; Haase, William; Dibben-Young, Arleone; Wolfe, Bret (Frontiers in Environmental Science, 2023)
Hawaiian coastal wetlands provide important habitat for federally endangered waterbirds and socio-cultural resources for Native Hawaiians. Currently, Hawaiian coastal wetlands are degraded by development, sedimentation, and invasive species and, thus, require restoration. Little is known about their original structure and function due to large-scale alteration of the lowland landscape since European contact. Here we used (1) rapid field assessments of hydrology, vegetation, soils, and birds, (2) a comprehensive analysis of endangered bird habitat value, (3) site spatial characteristics, (4) sea-level rise projections for 2050 and 2100 and wetland migration potential, and (5) preferences of the Native Hawaiian community in a GIS site suitability analysis to prioritize restoration of twelve coastal wetlands on the island of Molokaʻi. The site suitability analysis is the first to our knowledge to incorporate community preferences, habitat criteria for endangered waterbirds, and sea-level rise into prioritizing wetland sites for restoration. The rapid assessments showed that groundwater is a ubiquitous water source for coastal wetlands. A groundwater-fed, freshwater herbaceous peatland or “coastal fen” not previously described in Hawaiʻi was found adjacent to the coastline at a site being used to grow taro, a staple crop for Native Hawaiians. In traditional ecological knowledge, such a groundwater-fed, agro-ecological system is referred to as a loʻipūnāwai (spring pond). Overall, 39 plant species were found at the twelve sites; 26 of these were wetland species and 11 were native. Soil texture in the wetlands ranged from loamy sands to silt and silty clays and mean % organic carbon content was 10.93% ± 12.24 (sd). In total, 79 federally endangered waterbirds, 13 Hawaiian coots (‘alae ke‘oke‘o; Fulica alai) and 66 Hawaiian stilts (ae‘o; Himantopus mexicanus knudseni), were counted during the rapid field assessments. The site suitability analysis consistently ranked three sites the highest, Kaupapaloʻi o Kaʻamola, Kakahaiʻa National Wildlife Refuge, and ʻŌhiʻapilo Pond, under three different weighting approaches. The site prioritization represents both an actionable plan for coastal wetland restoration and an alternative protocol for restoration decision-making in places such as Hawaiʻi where no pristine “reference” sites exist for comparison.